2012
DOI: 10.1111/j.1467-7687.2012.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Class matters: 12‐month‐olds’ word–object associations privilege content over function words

Abstract: A fundamental step in learning words is the development of an association between a sound pattern and an element in the environment. Here we explore the nature of this associative ability in 12-month-olds, examining whether it is constrained to privilege particular word forms over others. Forty-eight infants were presented with sets of novel English content-like word-object pairings (e.g. fep) or novel English function-like word-object (e.g. iv) pairings until they habituated. Results indicated that infants as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 24 publications
2
25
0
1
Order By: Relevance
“…Importantly, the word form itself was kept constant, by selecting a target word form that was phonetically and phonotactically legal in both the native and foreign languages, and counterbalancing and cross‐splicing the same token into sentences from both languages. We tested 14‐month‐olds because, at this age, infants can reliably learn novel words in a laboratory setting (Byers‐Heinlein et al., ; MacKenzie et al., ,b; Schafer & Plunkett, ; Werker et al., ). Infants were trained on two novel word–object pairings, one in native sentence frames and one in foreign sentence frames.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the word form itself was kept constant, by selecting a target word form that was phonetically and phonotactically legal in both the native and foreign languages, and counterbalancing and cross‐splicing the same token into sentences from both languages. We tested 14‐month‐olds because, at this age, infants can reliably learn novel words in a laboratory setting (Byers‐Heinlein et al., ; MacKenzie et al., ,b; Schafer & Plunkett, ; Werker et al., ). Infants were trained on two novel word–object pairings, one in native sentence frames and one in foreign sentence frames.…”
Section: Methodsmentioning
confidence: 99%
“…Foreign word learning likely draws on many of the same capacities that support native word learning, and infants are remarkable word learners. Laboratory studies have shown that 12‐ to 14‐month‐old infants can rapidly form word–object associations (MacKenzie, Curtin, & Graham, ,b; Werker, Cohen, Lloyd, Casasola, & Stager, ). That is, even before infants can reliably produce words (Nazzi & Bertoncini, ), they are able to associate a label with its referent.…”
mentioning
confidence: 99%
“…It is well documented that infants' relatively open language learning systems become increasingly specified over the first two years of life (see Curtin & Zamuner, 2014, for a review). By 12 months of age, infants hold expectations about what constitutes an appropriate word form for an object label in their native language (Graf Estes, Edwards & Saffran, 2011; Hochmann, Endress & Mehler, 2010; MacKenzie, Curtin & Graham, 2012a, 2012b). For example, English-learning 12- and 18-month-olds are sensitive to the allowable sound sequences of English, and will learn words that conform to these legal sound patterns (Graf Estes et al , 2011; MacKenzie et al , 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…ooh ), or single consonantal sounds (e.g. /l/) to objects (MacKenzie et al ., 2012a; MacKenzie, Graham & Curtin, 2011; MacKenzie et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, hearing consistent labels allows monolingual infants as young as 3 months to form object categories (Balaban & Waxman, ; Ferry, Hespos & Waxman, ; Fulkerson & Waxman, ; Waxman & Braun, ). Further, in laboratory word learning tasks, 1‐year‐old monolinguals privilege word forms and sound combinations characteristic of their native language (Mackenzie, Curtin & Graham, , ; May & Werker, ). Other work with monolingual infants has revealed expectations that emerge over the second and third years of life that words are better labels for objects than gestures (Namy, ; Namy & Waxman, ).…”
Section: Discussionmentioning
confidence: 99%